Structural study of radiolytic catalysts Ni-Ce/Al2O3 and Ni-Pt/Al2O3. (January 2017) - Seridi, F.; Chettibi, S.; Keghouche, N.; Beaunier, P.; Belloni, J.
Abstract: Ni–Ce and Ni–Pt bimetallic catalysts supported over α-Al2 O3 are synthesized by using co-impregnation method, and then reduced, each via radiolytic process or thermal H2 -treatment. For Ni-Ce/Al2 O3, the structural study reveals that Ce is alloyed with Ni as Ce2 Ni7 nanoparticles in the radiation-reduced catalysts, while it segregates to the surface in the form of CeO2 in the H2 -reduced catalysts. For Ni-Pt/Al2 O3 radiolytic catalysts, Ni, Pt, NiPt and Ni3 Pt nanoparticles, which size is 3.5 nm, are observed. When the radiation-reduced samples are tested in the benzene hydrogenation, they both display high conversion rate. However, the Ni-Pt/Al2 O3 is more efficient than Ni-Ce/Al2 O3 . The performance of the catalysts is correlated with the high dispersion of the metal and the presence of intermetallic Ni–Pt and Ni–Ce phases. It is compared to that of other radiolytic monometallic/oxide catalysts of the literature. Graphical abstract: Highlights: Ni-Ce/Al2 O3 and Ni-Pt/Al2 O3 catalysts are reduced by γ-rays or H2 -treatment. Nanosized intermetallic compounds are formed in the radiation-reduced catalysts. Ce segregates as CeO2 in Ni-Ce/Al2 O3 (H2 ). None of bimetallic phases was detected. The radiolytic catalysts display high performances in the benzene hydrogenation.